2014
DOI: 10.1017/s1368980014001864
|View full text |Cite
|
Sign up to set email alerts
|

Rurality and dietary patterns: associations in a UK cohort study of 10-year-old children

Abstract: Objective: Despite differences in obesity and ill health between urban and rural areas in the UK being well documented, very little is known about differences in dietary patterns across these areas. The present study aimed to examine whether urban/rural status is associated with dietary patterns in a population-based UK cohort study of children. Design: Dietary patterns were obtained using principal components analysis and cluster analysis of 3 d diet records collected from children at 10 years of age. Ruralit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…In a Finnish national survey, children living in semi-urban areas had poorer diet quality than those in urban areas, as measured by the Finnish Children Healthy Eating Index (13) . In contrast, a regional survey in South West Britain found healthier dietary patterns in rural children compared with urban, including lower intake of snacks and processed food (14) .…”
mentioning
confidence: 79%
“…In a Finnish national survey, children living in semi-urban areas had poorer diet quality than those in urban areas, as measured by the Finnish Children Healthy Eating Index (13) . In contrast, a regional survey in South West Britain found healthier dietary patterns in rural children compared with urban, including lower intake of snacks and processed food (14) .…”
mentioning
confidence: 79%
“…The cause of differences other than similarities mentioned in the identified dietary patterns could be reported as differences between rural and urban environments, such as access to food, employment, and household income situation (27). Morris and Northstone (28) reported that rural children follow more traditional and healthier dietary patterns, while urban children follow more "fast and processed foods" dietary patterns in their study on a 10-year-old Cohort in the UK. This claim was also confirmed by mixed and traditional dietary patterns in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic investigations have identified how genetic traits have the potential to influence the domestic/personal environmental exposures, for example: where genetic propensity to armpit odour was linked to deodorant use 25 ; and an association between a single nucleotide polymorphism (SNP) in the oxytocin receptor gene to features of the maternal diet; 26 investigations assessing associations between health outcomes and workplace exposures. These indicated an association between paternal occupation and subfertility 27 and showed some weak evidence that certain maternal occupations were associated with low birth weights 28 ;investigations considering the impact of residential location and residential movement/migration on health and social outcomes, identifying associations between: residential rurality and diet; 29 the impact of underlying confounding factors to explain previously identified associations between residential movement and cannabis use, 14 residential stability and poor mental health; 30 and the impact of major life events on residential mobility; 31 investigations considering movements between places (e.g. the journey from home to school); identifying associations with fast-food consumption 32 and the role of mode of travel choices on activity levels; 33 conducting methodological work to develop environmental exposure modelling techniques within longitudinal research studies, including modelling particulate matter (PM 2.5 , PM 10 ) exposures and CO2 exposures; 12 , 34 neighbourhood measures (e.g.…”
Section: Data Resource Usementioning
confidence: 99%
“…investigations considering the impact of residential location and residential movement/migration on health and social outcomes, identifying associations between: residential rurality and diet; 29 the impact of underlying confounding factors to explain previously identified associations between residential movement and cannabis use, 14 residential stability and poor mental health; 30 and the impact of major life events on residential mobility; 31 …”
Section: Data Resource Usementioning
confidence: 99%